Modification of membrane lipids protects neurons against insulin resistance in models of Alzheimer's disease - Nordström, Viola; Herzer, Silke (Neuroforum, 2017)
Alzheimer's disease is a degenerative disease of the central nervous system, which leads to severe deficits in memory and orientation by a progressive loss of neurons and synapses. Soluble β-amyloid oligomers are highly neurotoxic precursors of β-amyloid fibrils that accumulate in Alzheimer’s disease. Binding of β-amyloid oligomers to synaptic insulin receptors leads to neuronal insulin resistance, which significantly contributes to cognitive impairments.